ADDRESSING GAPS IN SCHOOL FINANCIAL MANAGEMENT: THE ROLE OF TECHNOLOGY FOR PRIMARY SCHOOL TREASURERS - Rakhmatusakdiyah Rakhmatusakdiyah; Chusnul Chotimah; Imelda Dian Rahmawati; Hidayatulloh (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This research investigates the implementation of supervisory practices in increasing financial transparency and accountability of Islamic education institutions at Muhammadiyah 3 Pandaan Elementary School and Muhammadiyah 1 Candi Labschool Umsida Elementary School. Through a qualitative descriptive approach and using data collection, interviews, observation, and documentation, this research reveals that these two schools have involved structured planning, efficient fund management, and transparent reporting, significantly increasing the transparency and accountability of school finances. With continuous supervision and collaboration between various parties, both schools succeeded in ensuring effective and efficient use of funds. This research provides an understanding of financial supervision practices that can be carried out to increase financial transparency and accountability of Islamic educational institutions. The results are expected to provide guidance for other educational institutions interested in adopting similar reconnaissance approaches.